" The System Thinking As Approach For Developing The Training Process In Public Organizations" Proposed Vision - Hassanein, Abdel Rahim Mohamed Abdel Rahim (Journal of Economic, Administrative and Legal Sciences, 2018)
The research is focusing on the system thinking as an approach playing comprehensive view of the different dimensions of the issue or problem . The research focused on the importance of training in public organizations and the great efforts that the organizations doing for developing it, However the feedback from training indicates that the results is not commensurate with the objectives of the training process. The aim of this research focus on how to applying the system thinking as approach for developing the training process in public organizations. To achieve the research objectives, the descriptive analysis approach was used to analysis the previous studies and literatures in system thinking filed to formulate proposed vision. The main result in this research, the system thinking help the organizations to design effective training process to improve the performance and investment in intellectual capital. It important for the public organizations to adapted the proposed vision that mentioned in this research about applying the system thinking .